The Customer Relations Strategy CV. Total computer Sragen to Maintain Customer Loyalty in 2021 - Budi Kamiliya, Salsabila; Ishak, Aswad (Jogjakarta Communication Conference (JCC), 2023)
Business competition is one of the big risks that must be faced by a company. As the conditions on the CV. Total Computer Sragen as one of the companies in the field of Computerization or Information Technology (IT) is facing business competition with new competitors, especially in the Sragen Regency area. This paper will discuss the implementation carried out by CV. Total Computer Sragen can influence in maintaining customer loyalty through the presence of Word of Mouth (WoM). The method used in this study is a qualitative descriptive approach using data collection techniques to conduct interviews and documentation. The results of this study indicate that CV. Total Computer Sragen in implementing customer relations strategy by prioritizing information disclosure and the principle of one-day service in an effort to maintain customer loyalty. In the strategy carried out by the company, it provides customer visit services in an effort to provide customer satisfaction to the company.